Advantages & Disadvantages Of Mediation And Conciliation As An Industrial Relations Dispute Resolution Option - Sabela Gayo (International Asia Of Law and Money Laundering, 2023)
Since the birth of Law No. 2 of 2004 on industrial dispute resolution, the parties to the dispute have become easier and helped to resolve disputes between them. The instruments provided also become more diverse compared to the old rules. Such as mediation, conciliation and arbitration instruments. However, at the implementation stage, not many people understand the difference between dispute mediation and conciliation in terms of the origin and function of conciliation mediation has different characteristics as a passive mediator while in conciliation the conciliator is more active in resolving disputes. In the settlement of industrial disputes, mediation is used as the main instrument for resolving a wider scope than conciliation. Mediation can deal with disputes of rights, interests, termination of employment (layoffs) and disputes between unions within one company. Conciliation makes progress limited to conflicts of interest, termination, and disputes between unions in one company. Although in fact most of the industrial disputes involving rights disputes. The mediation and conciliation stationery comprehensively summarizes the advantages and disadvantages of each of these tools